Pengembangan Potensi Desa Krembangan dari Segi Pariwisata dan Olahan Jagung - Sasmita, Raymundo Patria Hayu (Lembaga Penelitian dan Pengabdian pada Masyarakat, 2021)
Currently , development is not only in urban but until the village .Development activities and community empowerment done to help ease a matter in the community .Potential of the village is a strength , the ability , and the owned and is likely to develop to bolster their people welfare. Krembangan village is one of the villages that can be further explored clearly hold their for their people welfare .Their potential in the village Krembangan is tourism and agriculture who also became one of primary search from the eyes of the people come from .The tourism sector the village are tourism objects Goa Kebon and yields namely secondary crops (corn , rice and other uses) .This journal discuss about the development of tourism objects Goa Kebon with the master plan of several facilities outbound in order to design and manufacturing agricultural products in the form of corn to be changed into a food processed some have economic value. Processing corn to processed foods such as popcorn and chips corn tortilla with using the equipment the kitchen simple but processed can produce value in the market with different kinds of in consideration of excess of these products.